Human cytochrome P-450PA (P-450IA2), the phenacetin O-deethylase, is primarily responsible for the hepatic 3-demethylation of caffeine and N-oxidation of carcinogenic arylamines. - Butler, M A (1989)
Aromatic amines are well known as occupational carcinogens and are found in cooked foods, tobacco smoke, synthetic fuels, and agricultural chemicals. For the primary arylamines, metabolic N-oxidation by hepatic cytochromes P-450 is generally regarded as an initial activation step leading to carcinogenesis. The metabolic activation of 4-aminobiphenyl, 2-naphthylamine, and several heterocyclic amines has been shown recently to be catalyzed by rat cytochrome P-450ISF-G and by its human ortholog, cytochrome P-450PA. We now report that human hepatic microsomal caffeine 3-demethylation, the initial major step in caffeine biotransformation in humans, is selectively catalyzed by cytochrome P-450PA. Caffeine 3-demethylation was highly correlated with 4-aminobiphenyl N-oxidation (r = 0.99; P less than 0.0005) in hepatic microsomal preparations obtained from 22 human organ donors, and both activities were similarly decreased by the selective inhibitor, 7,8-benzoflavone. The rates of microsomal caffeine 3-demethylation, 4-aminobiphenyl N-oxidation, and phenacetin O-deethylation were also significantly correlated with each other and with the levels of immunoreactive human cytochrome P-450PA. Moreover, a rabbit polyclonal antibody raised to human cytochrome P-450PA was shown to inhibit strongly all three of these activities and to inhibit the N-oxidation of the carcinogen 2-naphthylamine and the heterocyclic amines, 2-amino-6-methyldipyrido-[1,2-a:3',2'-d]imidazole and 2-amino-3-methylimidazo[4,5-f]-quinoline. Human liver cytochrome P-450PA was also shown to catalyze caffeine 3-demethylation, 4-aminobiphenyl N-oxidation, and phenacetin O-deethylation. Thus, estimation of caffeine 3-demethylation activity in humans may be useful in the characterization of arylamine N-oxidation phenotypes and in the assessment of whether or not the hepatic levels of cytochrome P-450PA, as affected by environmental or genetic factors, contribute to interindividual differences in susceptibility to arylamine-induced cancers.